The Trump administration and outer space: promoting US leadership or heading towards isolation?. Issue 5 (3rd September 2018) - Tronchetti, Fabio; Liu, Hao
ABSTRACT: In a relatively short period of time, the Trump administration has been fairly active in the field of space. The reconstitution of the National Space Council, under the direction of Vice President Pence, the President's signing of Space Policy Directive 1, that calls for the return of humans to the Moon, and the announcement of a National Space Strategy that calls for an 'America first' approach in space, have been the highlights of this process. A key component of the administration's approach has been the promotion of commercial (private) space activities through an effort of regulatory reform intended to facilitate free enterprise and individual initiative in space. Overall, it is evident that the Trump administration views a consolidated US leadership in space as instrumental to 'Make America Great Again'. However, due to the lack of cohesion in the management of the US space program, the controversial interpretation of international principles and the US-centred view of space endorsed by the administration, doubts remain as to whether the space policy of the Trump administration will foster US leadership in space or lead to its progressive isolation.